The Effects of the Biological Agents Infliximab, Vedolizumab, and Ustekinumab on Intestinal Anastomosis: An Experimental Study in Rats - Alexandra Menni; Georgios Tzikos; Patroklos Goulas; George Chatziantoniou; Angeliki Vouchara; Athanasios S. Apostolidis; Aristeidis Ioannidis; Georgios Germanidis; Lyssimachos G. Papazoglou; Olga Giouleme; Stylianos Apostolidis (Biomedicines)
Background/Objectives: The potential side effects of the use of biological agents in the perioperative period are still under investigation. This animal prospective study aimed to evaluate the overall impact of biological factor administration after intestinal surgery. Methods: This study included 80 female Wistar rats sorted into four groups: three groups received one of the biological factors, infliximab, vedolizumab, or ustekinumab; the control group received placebo therapy. After enterotomy and intestinal anastomosis, the bursting pressure (BP) of the anastomosis was compared among the groups on postoperative days (PODs) 3 and 7. Results: On POD3, the control group presented with a significantly higher mean BP (154.6 ± 39.7 mmHg) compared to the infliximab (66.8 ± 10.4 mmHg), vedolizumab (105.4 ± 37.6 mmHg), and ustekinumab (98.8 ± 47.9 mmHg) groups. A post hoc analysis among the three biological agent groups revealed differences only when comparing infliximab and vedolizumab rats with the controls on POD3 (p < 0.001) and with the ustekinumab rats on POD7, having a greater mean BP (282.5 ± 80.1 mmHg, p = 0.031). No differences were observed regarding the event of broken anastomosis among the four groups. Conclusions: This experimental study’s findings highlight the varying detrimental effects of different biological agents on the strength of intestinal anastomosis, with ustekinumab demonstrating superior performance.